Molecular Mechanisms Regulating Ontogeny of O2- and CO2-Chemosensitivity in Rat Adrenomedullary Chromaffin Cells: Role of Nicotinic ACh and Opioid Receptor Signalling - Salman, Shaima (My University, 2013)
Catecholamine (CAT) secretion from adrenomedullary chromaffin cells (AMCs) is essential for survival of the fetus and for adaptation of the newborn to extrauterine life. CAT secretion protects the fetus from intrauterine hypoxia (low O2) and is required for maintaining cardiac conduction and preparing the lungs for air breathing. Asphyxial stressors (e.g. hypoxia, hypercapnia (high PCO2), and acidosis (low pH)) arising from labor contractions and postnatal apneas, are the main stimuli for the ‘non-neurogenic’ CAT release from perinatal AMCs. In the rat, the mechanisms of hypoxia chemosensitivity in AMCs involve inhibition of a variety of K+ channels, leading to membrane depolarization, voltage-gated Ca2+ entry, and CAT secretion. The magnitude of this depolarization is regulated by the simultaneous activation of ATP-sensitive K+ (KATP) channels, which tends to hyperpolarize the membrane potential during hypoxia. Interestingly, chemosensitivity of rat AMCs and CAT secretion in response to asphyxial stressors are markedly reduced postnatally following the development of functional innervation of these cells by the splanchnic nerve.
The primary purpose of this thesis was to delineate molecular mechanisms involved in the suppression of hypoxia and hypercapnia chemosensitivity following splanchnic innervation in neonatal rat AMCs. Experiments were designed to test the general hypothesis that the ontogeny of O2 and CO2 sensitivity in AMCs is regulated by the activation of postsynaptic nicotinic ACh and opioid receptor signalling pathways following innervation. Previous studies in this laboratory showed that exposure of perinatal rat AMCs to nicotine in utero and in vitro resulted in the selective blunting of hypoxia (but not hypercapnia) chemosensitivity. The underlying mechanism was attributable to the increased membrane hyperpolarization caused by the functional upregulation of KATP channels. In Chapter 2, I report the results of investigations of molecular mechanisms involved in the nicotine-induced upregulation of KATP channels, using a rat fetal-derived, O2- and CO2-sensitive immortalized chromaffin cell line (MAH cells), as a model. Exposure of MAH cells to chronic nicotine (50 μM) for 7 days in culture caused an increase in the expression of the KATP channel subunit, Kir6.2. This effect was blocked by α-bungarotoxin, a blocker of homomeric α7 nicotinic acetylcholine receptors (α7 nAChRs). The upregulation of Kir6.2 in MAH cells was also dependent on the transcription factor, hypoxia inducible factor (HIF)-2α. First, whereas the upregulation of Kir6.2 was present in wild type and scrambled control MAH cells, it was absent in HIF-2α-deficient (shHIF-2α) MAH cells. Second, chronic nicotine caused a progressive, time-dependent increase in HIF-2α accumulation that occurred in parallel with the increase in Kir6.2 expression. Third, chromatin immunoprecipitation (ChIP) assays revealed the binding of HIF-2α to a hypoxia response element (HRE) in the promoter region of the Kir6.2 gene. These data suggest that chronic nicotine causes the accumulation of HIF-2α which results in the transcriptional upregulation of the Kir6.2 gene. These observations were validated in an in vivo model where rat pups were exposed to nicotine in utero. Western blot analysis of adrenal gland tissues from nicotine-exposed (relative to saline-exposed) pups revealed a significant increase in Kir6.2 subunit expression and HIF-2α accumulation, and both were restricted to the medullary (but not cortical) tissue.
Chapter 3 tested the hypothesis that postnatal innervation causes the suppression of O2- and CO2-chemosensitivity in neonatal AMCs via opioid receptor signalling. It was found that chronic μ- and δ-opioid agonists (2 μM) in vitro led to the suppression of both O2- and CO2-chemosensitivity; this was correlated with the upregulation of KATP channel expression and the downregulation of carbonic anhydrase (CA) I and II respectively. The underlying molecular and signalling mechanisms were further investigated in Chapter 4. Using the MAH cell model, it was found that exposure to a combination of μ- and δ-opioid agonists for 7 days resulted in the naloxone-sensitive upregulation of Kir6.2 subunit and the downregulation of CAII. Similar to chronic nicotine exposure, the effects of chronic opioids on the upregulation of Kir6.2 and downregulation of CAII were HIF-2α-dependent. Western blot analysis revealed that HIF-2α accumulation in opioid-treated MAH cells occurred along a time-course that paralleled the upregulation of Kir6.2 subunit. ChIP assays demonstrated the binding of HIF-2α to the promoter region of the Kir6.2 subunit gene in opioid-treated MAH cells. Moreover, PKA activity (but not PKC or CaMK) was found to be required for the effects of opioids on Kir6.2 and CAII expression, but not HIF-2α accumulation. In complementary in vivo studies, adrenomedullary tissues from morphine-exposed rat pups showed an increased expression of both HIF-2α and Kir6.2, and decreased expression of CA1 and II protein. These findings have uncovered novel mechanisms by which postnatal innervation contributes to the ontogeny of O2- and CO2-chemosensitivity in rat adrenal chromaffin cells. They also suggest mechanisms by which exposure of the fetus to nicotine in cigarette smoke or opioids from drug abuse might contribute to abnormal arousal reflexes, and pathophysiological conditions such as Sudden Infant Death Syndrome (SIDS).
Keywords: Opioids; Nicotine; Katp channel; HIF; SIDS; Life Sciences; Medicine and Health Sciences; Life Sciences